Adaptasi dan Uji Psikometri Alat Ukur Perilaku Ramah Lingkungan Versi Indonesia - Adishesa, Made Syanesti; Rocky; Suwartono, Christiany (Journal of Research and Measurement in Psychology: JPPP, 2024)
Environmentally-friendly behavior is widely studied in Indonesia. However during the last 5 years, there has not yet been a study focusing on testing the psychometric properties of such measure. The main purpose of this study is to adapt an instrument to measure environmentally-friendly behavior and to examine the reliability and validity of the Indonesian translation of the scale. The sample composed of 196 adults with age range 18-25 years old. The original version contained 10 items. The final version of the translated scale contained five items, which showed a reliability coefficients of 0.78. The reasons for the elimination of items in the translated version are discussed. Moreover, the results of the factor analysis confirmed the fit of the model measuring a single factor, namely environmentally-friendly behavior. Ultimately, it was determined that the Indonesian version of the Environmentally-Friendly Behavior is a reliable and valid scale.